Modelling and forecasting energy demand of Bangladesh using AI based algorithms - Mahmud, Booshra Nazifa; Ferdoush, Zannatul; Mim, Lamia Tasnim (Brac University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2019.